Long-term persistence in protection and response to a hepatitis B vaccine booster among adolescents immunized in infancy in the western region of China - Zhen-Zi Wang; Yu-Hua Gao; Wei Lu; Cun-Duo Jin; Ying Zeng; Ling Yan; Feng Ding; Tong Li; Xue-En Liu; Hui Zhuang (Taylor & Francis Group, 2017)
Objectives: To evaluate the persistence of protection from hepatitis B (HB) vaccination among adolescents immunized with a primary series of HB vaccine as infants, and the immune response to booster doses. Methods: Healthy adolescents aged 15-17 y vaccinated with HB vaccine only at birth were enrolled. Baseline serum hepatitis B surface antigen (HBsAg), antibody against hepatitis B surface antigen (anti-HBs) and antibody against hepatitis B core antigen (anti-HBc) were detected by Enzyme-Linked Immunosorbent Assay (ELISA) and anti-HBs level was measured using Chemiluminescent Microparticle Immunoassay (CMIA). The rate of HBV infection was calculated. The seroprotection rate of anti-HBs (≥ 10 mIU/ml) and GMC level were used to evaluate the persistence of immunity from HB vaccination. Those with anti-HBs < 10 mIU/ml were immunized with booster doses of HB vaccine and the anamnestic response was assessed. Results: Of 180 adolescents who received a primary series of HB vaccinations as infants, 3 (1.7%) had HBV infection and 74 (41.1%) had anti-HBs ≥ 10 mIU/ml with a GMC of 145.11 mIU/ml. The remaining 103 (57.2%) with anti-HBs < 10 mIU/ml received a booster dose of 20 μg HB vaccine and achieved the seroprotection rate of 84% (84/100) and a GMC of 875.19 mIU/ml at one month post-booster. An additional dose of 60 μg HB vaccine was administered to the 16 adolescents with anti-HBs < 10 mIU/ml after the first booster. All of them obtained anti-HBs seroprotection with a GMC of 271.02 mIU/ml at 1.5 months after an additional dose. Conclusions: Vaccine-induced immunity persisted for up to 15-17 y in 89.3% (158/177) of participants after a primary HB vaccination in infancy. Administering a booster dose of 20μg HB vaccine elicited an anamnestic immune responses in the majority of individuals with baseline anti-HBs <10 mIU/ml.